Sheikh Farid-ud-Din Shakar Ganj (1188–1280): A Historical Study - Muhammad Hassan; Momina Manzoor; Asif Naveed (Social Science Review Archives, 2025)
This research paper assesses the life, teachings and Sufi legacy of Sheikh Farid-ud-Din Shakar Ganj (1188–1280), who was a highly respected Sufi saint of the Chishtia Order and left a deep mark on the spiritual, social, and cultural life of medieval South Asia. In this section of the research, a qualitative analysis approach is applied to assess the crucial role played by Sheikh Farid-ud-Din Shakar Ganj as he was born in Kothiwal, Multan, and later settled in Ajodhan (now Pakpattan), where he spent his life guiding people towards God and teaching moral and spiritual values. He lived a life of devotion, simplicity, and humility, showing that true closeness to God came through love, patience, and service to others. He also encouraged spiritual music, called Sama, as a way for people to feel God’s presence, following the example of great saints like Khwaja Moun-ud-din Chishti. His poetry, written in Punjabi in form of Shalook, Persian, and Arabic, carried deep spiritual lessons and practical advice for daily life. Through his verses, he spoke about God’s love, human mortality, humility, and ethical behavior. Stories from his life, such as his teaching that helping the hungry is like a “sixth pillar of Islam,” show how he combined spiritual wisdom with care for ordinary people. He taught that devotion is not just about rituals, but about compassion, kindness, and living a moral life. Baba Farid’s influence is still alive today. The question that has been answered through this research paper is that in what way his teachings, Punjabi poetry continued to inspire and attract towards his shrine in Pakpattan, a thousands of pilgrims every year, and the values he taught remain part of South Asian Sufi culture. Further, this study highlights his life, teachings, and poetry in the context of medieval Punjab, showing how Baba Farid’s guidance brought people closer to God while promoting love, service, and social harmony. He remains a timeless example of a saint whose wisdom touched hearts and shaped communities.